Understanding the effect of exposure of human pathogens to polluted surface water: Vibrio cholerae as a model organism - Islam, Syeda Sumaiya (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2018.